3+(x-2)-3x=3(4x-2)

Simple and best practice solution for 3+(x-2)-3x=3(4x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+(x-2)-3x=3(4x-2) equation:


Simplifying
3 + (x + -2) + -3x = 3(4x + -2)

Reorder the terms:
3 + (-2 + x) + -3x = 3(4x + -2)

Remove parenthesis around (-2 + x)
3 + -2 + x + -3x = 3(4x + -2)

Combine like terms: 3 + -2 = 1
1 + x + -3x = 3(4x + -2)

Combine like terms: x + -3x = -2x
1 + -2x = 3(4x + -2)

Reorder the terms:
1 + -2x = 3(-2 + 4x)
1 + -2x = (-2 * 3 + 4x * 3)
1 + -2x = (-6 + 12x)

Solving
1 + -2x = -6 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
1 + -2x + -12x = -6 + 12x + -12x

Combine like terms: -2x + -12x = -14x
1 + -14x = -6 + 12x + -12x

Combine like terms: 12x + -12x = 0
1 + -14x = -6 + 0
1 + -14x = -6

Add '-1' to each side of the equation.
1 + -1 + -14x = -6 + -1

Combine like terms: 1 + -1 = 0
0 + -14x = -6 + -1
-14x = -6 + -1

Combine like terms: -6 + -1 = -7
-14x = -7

Divide each side by '-14'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| -46-(-34)=X/4 | | 7x-4(x-3)=2y | | 5r-6=69 | | x+x-12%=47 | | 3x^2+5x-2x=0 | | 4b-6=8(-8+10b) | | y^3-X^3=91 | | (3a+4)2= | | -14p^2-17p+6= | | (4a-5)(4a+5)= | | 2x-(x+2)+2x-4=12 | | -4(u-4)=6u+36 | | 3t^4+8t^3+4t^2=0 | | 2m+5n+8m+7n= | | -5u+45=-2(u-9) | | 0.6(x-1)+0.2=6.6 | | -8(y-8)=2y-36 | | 2x-3=4-5x | | (6x^2+8x+12)-(4x^2+3x-2)= | | (3a^2-9a)+(12a^2+5a)= | | 13y-4y=27 | | (2+x)=(x*2) | | 2a+8=7a-5 | | 2.5*2x= | | 0.5x+12.3=7.1-1.1x | | (9x^2+6x+3)+(4x^2-8x+4)= | | 6c^2+21c-4c-14= | | (x+2)2+(y-6)2=25 | | 2x^2+5*2x= | | 3a(5a^2+8a)= | | -5x+7=3x+7 | | 14=6(y-2)+7y |

Equations solver categories